Soldiering in the Army of Northern Virginia : a statistical portrait of the troops who served under Robert E. Lee - Glatthaar, Joseph T., 1956- (Civil War America (Series), 2011)
This quantitative study provides a narrative and statistical analysis of many key aspects of General Robert E. Lee's Army of Northern Virginia. Serving as a companion to the author's 'General Lee's Army: From Victory to Collapse', it presents his supporting data and major conclusions in extensive detail. While gathering research materials for 'General Lee's Army', the author compiled quantitative data on the background and service of 600 randomly selected soldiers - 150 artillerists, 150 cavalrymen, and 300 infantrymen - affording him insight into the pre-war and wartime experience of Lee's troops.